Differences in exopolysaccharides of three microbial aggregates. Issue 19 (24th August 2022) - Yang, Fan; Li, Hanxiang; Wang, Shuai; Zhao, Fan; Fang, Fang; Guo, Jinsong; Long, Man; Shen, Yu
ABSTRACT: Different microbial aggregates show substantial differences in morphology, and extracellular polymer substances have been confirmed to play a key role in the formation of aggregates. In this study, three different microbial aggregates and their exopolysaccharides were compared. The results show that the granular sludge was largest in size and the most compact in shape. Biofilms with a certain thickness had the next greatest density, and flocculent sludge, with the smallest particle size, was the loosest. The extended Derjaguin-Landau-Verwey-Overbeek analysis shows that hydrogen bonding, hydrophobic and electrostatic interactions affect the aggregation of microorganisms. A comparison of exopolysaccharides shows that granular sludge exopolysaccharides show the highest hydrophobicity (38.08%) and lowest surface charge (−20.5 mV), followed by biofilm exopolysaccharides (27.9% and −24.8 mV respectively). The results of Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy show that the contents of hydrophilic and hydrophobic functional groups and charged functional groups of exopolysaccharides affect the above properties of exopolysaccharides, thereby affecting microbial aggregation. In addition, the hydrogen bond content of exopolysaccharides in granular sludge (19.3%), biofilm (19.2%) and activated sludge (18.9%) decreased sequentially. This also affects the cross-linking of microbial exopolysaccharides to form hydrogels. Finally, the results of confocal laser scanning microscopy showed that, different from the other two aggregates, the extracellular α-polysaccharides of granular sludge are mainly distributed in the nucleus, which is more conducive to aggregation. The research results of this thesis provide a new understanding of the differences in the aggregation morphology of different aggregates from the perspective of exopolysaccharides. GRAPHICAL ABSTRACT: UF0001